The Formulation and Antioxidant Activity Test of Binahong (Anredera cordifolia) Leaves Extract Lotion - Hasty Hamzah; Yuyun Wirasasmita; Wa Ode Syafriah (Halu Oleo University, 2022)
Background: With current wide range of scientific research regarding the benefits of antioxidants, many has tried to invent new sources of this compound. The use of plant-based source for antioxidants recently become more and more popular, and one of these plants is Binahong (Anredera cordifolia). The leaves of these plant had been analyzed before to contain antioxidant compound. Objective: This research aimed to test, based on previous claim of antioxidant activity of Binahong (Anredera cordifolia) leaves. Methods: The lotion used was formulated using Tween 60 and Span 60 as its emulgator. After test, it was determined that the emulsion type is water in oil (w/o). Before Binahong Leaves extract were incorporated, the lotion was tested for physical stability including organoleptics, emulsion type, pH determination, homogeneity, and viscosity. Results: The analysis for antioxidant activity by DPPH method of Binahong leaves extract with various concentrations of 12,5 μg/mL, 25 μg/mL, 50 μg/mL, 100 μg/mL, 200 μg/mL, 400 μg/mL, yield a value of IC50 822.22 µg/mL (mild antioxidant activity level). This result corroborates previous findings with the same result. Meanwhile, the lotion containing Binahong leaves extract with various concentrations of 25 μg/mL, 50 μg/mL, 100 μg/mL, 200 μg/mL, 400 μg/mL, 800 μg/mL were analyzed with same method and yield a value of IC50 27041.50 µg/mL. Conclusion: The result proved there was a further loss of antioxidant activity after the extract were incorporated into lotion. Keywords: Formulation, Anredera cordifolia, Antioxidant, Antioxidant Lotion, Binahong,